Long-term results of intra-arterial onyx injection for type II endoleaks following endovascular aneurysm repair. (June 2017) - Ribé, L; Bicknell, CD; Gibbs, RG; Burfitt, N; Jenkins, MP; Cheshire, N; Hamady, M
Purpose: The aim of this paper is to report our experience of type II endoleak treatment after endovascular aneurysm repair with intra-arterial injection of the embolizing liquid material, Onyx liquid embolic system. Methods: From 2005 to 2012, we performed a retrospective review of 600 patients, who underwent endovascular repair of an abdominal aortic aneurysm. During this period, 18 patients were treated with Onyx for type II endoleaks. Principal findings: The source of the endoleak was the internal iliac artery in seven cases, inferior mesenteric artery in seven cases and lumbar arteries in four cases. Immediate technical success was achieved in all patients and no endoleak from the treated vessel recurred. During a mean follow-up of 19 months, no major morbidity or mortality occurred, and one-year survival was 100%. Conclusions: Treatment of type II endoleaks with Onyx is safe and effective over a significant time period.